2020
DOI: 10.4314/gmj.v53i4.2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating services for perinatal asphyxia and low birth weight at two hospitals in Ghana: a micro-costing analysis

Abstract: Background: Neonatal mortality has been decreasing slowly in Ghana despite investments in maternal-newborn services. Although community-based interventions are effective in reducing newborn deaths, hospital-based services provide better health outcomes. Objective: To examine the process and cost of hospital-based services for perinatal asphyxia and low birth weight/preterm at a district and a regional level referral hospital in Ghana. Methods: A cross-sectional study was conducted at 2 hospitals in Greater Acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Another important guideline is proper infection prevention measures within neonatal units. Studies [259][260][261][262][263][264][265][266] have shown that implementing strict hand hygiene protocols significantly reduces infection rates among neonates. In resource-limited settings like West Africa, where access to clean water and sanitation facilities may be limited, it becomes even more crucial to prioritize infection prevention measures within neonatal units.…”
Section: Evidence-based Guidelines For Neonatal Care In West Africamentioning
confidence: 99%
“…Another important guideline is proper infection prevention measures within neonatal units. Studies [259][260][261][262][263][264][265][266] have shown that implementing strict hand hygiene protocols significantly reduces infection rates among neonates. In resource-limited settings like West Africa, where access to clean water and sanitation facilities may be limited, it becomes even more crucial to prioritize infection prevention measures within neonatal units.…”
Section: Evidence-based Guidelines For Neonatal Care In West Africamentioning
confidence: 99%
“…To date, a number of hospital-based interventions targeting improved newborn care in sub-Saharan Africa have been assessed for cost-effectiveness, yet a gap remains in the current literature around costs associated with systems-strengthening activities. Rather, much of the existing research focuses on service-based or provider-level interventions [15][16][17][18]. For example, cost analysis of an aligned clinician-training intervention, part of MEBCI implementation in other regions, found that the cost per capita was 984 United States Dollars (US $)-a significant overall cost [19].…”
Section: Introductionmentioning
confidence: 99%